Elisitasi Kebutuhan Pengguna Menggunakan Metode Storyboard - Ani Tri Wahyuningsih; Wahyu Andhyka Kusuma (Teknik Informatika Universitas Pamulang, 2021)
The COVID-19 pandemic requires online learning for all educational units including University of Muhammadiyah Malang. The University of Muhammadiyah Malang uses https://lms.umm.ac.id/ as a media to support the process of online learning. The use of https://lms.umm.ac.id/ has been going for a few months, but the students are still confused about the features provided on the site. This might happen because of the sudden change from the previous media which is https://elmu.umm.ac.id/login/canvas. The LMS used is still at the development stage by the academic admin of the University of Muhammadiyah Malang. For the software development process, the developer is required to make a high quality software that meet the users need. Requirement elicitation technique is one of important factors to determine the quality of a software. There are many techniques that can be used in the requirement elicitation process. This study uses the storyboard technique to explore user needs for the use of https://lms.umm.ac.id/ during online learning. Based on the research that has been done, the researcher concludes that the use of storyboarding techniques in exploring user needs in the LMS development process is considered easier. In this problem, a solution was found in the form of adding a feedback feature that was used to measure students' understanding of the learning material and the tasks given during online learning.